Evaluation of Pollen Samples of Inducer Line with Different Techniques and Pollen Size Effect on Haploid Seed Formation in Maize - Gülizar PINAR; Fatih KAHRIMAN (ISPEC Journal of Agricultural Sciences)
There is an urgent need to evaluate and optimize use of different sized pollen grains of inducer lines to increase haploid seed production in maize breeding programs. Therefore, this study aimed to evaluate the effect of pollen size on haploid seed production in maize under greenhouse conditions to characterize pollen samples taken from an inducer maize line by morphological, molecular and spectrophotometric measurements. Three donors and one inducer line were used as the experimental material. The pollen samples of inducer line were collected and filtered into two different sizes (50µ and 100µ) using a special vacuum filtration device. Morphological measurements based on image analysis were made, spectral data were collected in Near Infrared Reflectance (NIR) and Raman spectroscopy devices. The protein bands were examined with SDS-PAGE analysis on the collected pollen and seed samples. Haploid induction rates of the seed samples obtained after pollination of donor materials with sized-pollen samples were determined. The results of the study indicated spectral and molecular differences in the pollen samples separated by 50 and 100µ filters. Haploid induction rate (HIR) values ranged 7.40% -18.9% in the used donors, however higher haploid seed formation was observed in small-sized pollen samples compared to the others.